2022
DOI: 10.1093/sleep/zsac036
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing and aspiration during sleep in patients with obstructive sleep apnea versus control individuals

Abstract: Study Objectives There are only a few reports on voluntary swallowing during sleep; therefore, this study aimed to propose a method for observing voluntary swallowing during sleep using polysomnography. The frequency of voluntary swallowing during sleep and the factors related to swallowing and aspiration during sleep were investigated. Methods Polysomnography records of 20 control subjects and 60 patients with obstructive sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
1
1
Order By: Relevance
“…In the present study, the results showed that the higher the position of the hyoid bone, the more likely it was to cause choking and cough reflex during eating and drinking. In general, it is believed that in older adults, the suprahyoid muscle group relaxes, the position of the hyoid bone decreases, and the force to pull up the hyoid bone weakens, resulting in decreased swallowing function and increased susceptibility to aspiration, often accompanied by other complications [3,6,10,21,22]; however, the results of the present study contradict this hypothesis.…”
Section: Plos Onecontrasting
confidence: 75%
“…In the present study, the results showed that the higher the position of the hyoid bone, the more likely it was to cause choking and cough reflex during eating and drinking. In general, it is believed that in older adults, the suprahyoid muscle group relaxes, the position of the hyoid bone decreases, and the force to pull up the hyoid bone weakens, resulting in decreased swallowing function and increased susceptibility to aspiration, often accompanied by other complications [3,6,10,21,22]; however, the results of the present study contradict this hypothesis.…”
Section: Plos Onecontrasting
confidence: 75%
“…Kohno et al examined the frequency of swallowing during sleep using the muscle activity of swallowing-related muscles as an index of swallowing and reported that it was significantly higher in patients with OSA (6.6 ± 3.8 times/h) than in those without (4.1 ± 2.2 times/h) [42]. They also focused on respiratory arrest during swallowing (swallowing apnea) and defined incomplete swallowing as swallowing activity without swallowing apnea, which was significantly more frequent in patients with OSA.…”
Section: Complications With Dysphagiamentioning
confidence: 99%